Iron biofortification and homeostasis in transgenic cassava roots expressing an algal iron assimilatory protein, FEA1 - Ihemere, Uzoma; Narayanan, Narayanan; Sayre, Richard (Frontiers in Plant Science, 2012)
We have engineered the starchy root crop cassava (Manihot esculenta) to express the Chlamydomonas reinhardtii iron assimilatory protein, FEA1, in roots to enhance its nutritional qualities. Iron levels in mature cassava storage roots were increased from 10 to 36 ppm in the highest iron accumulating transgenic lines. These iron levels are sufficient to meet the minimum daily requirement for iron in a 500 gm meal. Significantly, the expression of the FEA1 protein did not alter iron levels in leaves. Transgenic plants also had normal levels of zinc in leaves and roots consistent with the specific uptake of iron mediated by the FEA1 protein. Relative to wild-type plants, FEA1 expressing plants had reduced Fe(III) chelate reductase activity and gene expression levels consistent with the more efficient uptake of iron in FEA1 transgenic plants. We also show that genes involved in iron homeostasis in cassava have altered tissue-specific patterns of expression in transgenic plants. Steady state transcript levels of the metal-chelate transporter MeYSL1, and the iron storage proteins, MeFER2 and MeFER6, were elevated in various tissues of FEA1 transgenic plants compared to wild-type plants. These results suggest that these gene products play a role in iron translocation and homeostasis in FEA1 transgenic cassava plants. These results are discussed in terms of enhanced strategies for the iron biofortification of plants.